DEVELOPMENT OF THE GEOPOLITICAL SITUATION IN CENTRAL ASIA THROUGH THE PRISM OF UKRAINIAN NATIONAL INTERESTS - KUZNETSOV, Viktor (CENTRAL ASIA AND THE CAUCASUS, 2004)
At the end of the 20th century, Central Asia became the main intersection of the political processes going on in the world and the arena for a latent confrontation between the largest states. The main strategic rivals—the U.S., Russia, and China—are interested in forming their own security structure and are striving to take personal control over the region’s raw materials and energy resources, as well as over the transcontinental communication lines that link Europe with Asia. As a result of the antiterrorist campaign in Afghanistan, Central Asia has become a zone of Washington’s permanent global interests. On 13 December,2001, Elizabeth Jones, Assistant Secretary for Euro-pean and Eurasian Affairs, said in her testimony before the Senate Foreign Relations Committee’s Subcommittee on Central Asia and the Caucasus:After this conflict is over, we will not abandon Central Asia. We are committed to providing the re-sources, the high-level attention, and the multinational coordination to support reform opportunities.we want to stand by the Central Asian countries in their struggle to reform their societies in the same way they have stood by us in the war on terrorism.”1 In other words, the antiterrorist campaign gave the U.S. a legitimate opportunity to implement its long-term foreign policy strategy. Having incorporated the states of Central Asia and the Southern Caucasus into its zone of “vitally important interests, "Washington began implementing Zbigniew Brzezinski’s geostrategic conception. And its goal is “to help ensure that no single power comes to control this geopolitical space and that the global community has unhindered financial and econom-ic access to it.”2 Since the United States is actively building its new regional strategy and security system, Russia and China have been forced to step up the forma-tion of their own geopolitical space in the region by reviewing the national defense systems here. In this way, American geostrategy in the region is creat-ing a new configuration of interrelations in the U.S.-RF-PRC format, which will inevitably lead to more intense competition and to new contradictions based on the changing geopolitical and geo-economic priorities regarding expansion of the global markets. The Ukrainian president’s visit to Central Asia in 2003 showed that Kiev is interested in developing constructive relations with its republics and although Ukraine possesses enough potential to expand interstate cooperation in different areas, it does not have the opportunity on its own, given its insufficient economic and military resources, to have a significant influence on the geopolitical situation in this region, which Kiev should keep in mind if it wishes to strengthen contacts with the countries here.